Study of Medical Regulation of Euthanasia - S, Chuluunsukh.; Kh, Damdinjav.; Ts, Tvwshinjargal.; M, Tserenbat. (Caucasus Journal of Health Sciences and Public Health, 2020)
Euthanasia is one of the most sensitive issues directly related to the right to life, and it is a topic that directly affects the social psychology of deciding whether a person will live or die in the future. As a component of multifaceted social relations, euthanasia is a complex concept that includes ethics, medicine, legal science, and religious and customary norms. The issue of euthanasia, which arises from the development trends and trends in legal studies in our country and abroad, has always been raised, but has not yet been resolved. The Mongolian Health Law and other medical legal acts do not prohibit euthanasia, and the right to refuse treatment is openly regulated, but from a criminal point of view, euthanasia is prohibited under criminal law. For example, if a doctor performs euthanasia with the consent of a client or his / her relatives, he / she will be considered a criminal and sentenced to 8-15 years in prison under Article 10.1 of the 2015 Criminal Code of Mongolia. Moreover, the 2010 Supreme Court’s General Interpretation states that the killing of a victim with the victim’s consent should be categorized as such. Currently, the following countries around the world support Active Euthanasia. These are: the Netherlands / 2002 /, France / 2004 /, Switzerland / 2005 /, Luxembourg / 2009 /, Canada / 2016 /, Belgium / 2014 /, Italy / 2018 /, Oregon / 1998 /, Montana / 2008 /, Washington / 2009 /, Vermont / 2013 /, California / 2015 /, Colorado / 2016 /, Germany / 2015 /, Colombia / 2015 /, Australia / 2019 /, and the number of countries supporting euthanasia is increasing year by year. There are also 60 countries in the world that have legalized inactive euthanasia, including India (2011), Israel (2005), South Korea (2016), and Mexico (2008), and Mongolia issued Order No. 446 on November 25, 2013. , guaranteeing the right to refuse service is the legalization of inactive euthanasia. There has been no comprehensive medical and legal study to determine the knowledge and attitudes of physicians and caregivers of patients about the legal environment, and palliative care has been developed in Mongolia for 20 years. On the other hand, the development of a democratic society raises the issue of human rights at a time when human rights issues are on the rise.